Natural outcrossing in cocona - Paiva, Waldelice Oliveira de (Pesquisa Agropecuaria Brasileira, 1999)
In order to evaluate the natural rates of outcrossing in cocona (Solanum sessiliflorum Dunal), two cultivars, one with antocyanin presence and other without antocyanin, were planted in Manaus, AM, Brazil. The percentage of cross-polination was evaluated in three plant flowering periods and was estimated in 31%. During the period of cultivation, high presence of beas of Apidae genus Paratrigona, Trigona and Melipona and beetle Crysomelidae were observed.